Advances in Natural Fibre Composites Raw Materials, Processing and Analysis (Springer International Publishing, 2018)
This book presents selected high-quality research papers submitted to ICNF 2017, the 3rd International Conference on Natural Fibers, which was held in Braga, Portugal, on 21-23 June 2017. It discusses the latest research and developments in the field and covers a wide range of topics related to various aspects of natural-fiber composites, such as production and processing of raw materials, surface modification and functionalization, advanced fibrous structures for composites, nano fibers, experimental characterization, modeling and analysis, design and product development, applications, market potential, and environmental impacts. The book presents the latest research work addressing different approaches and techniques to improve processing, performance, functionalities and cost-effectiveness of natural-fibers composites, in order to increase their applications in different industrial sectors such as automobiles, transportation, construction, and sport. & nbsp; .